In the field: exploiting the untapped potential of immunogenic modulation by radiation in combination with immunotherapy for the treatment of cancer - Kwilas, Anna; Donahue, Renee N.; Bernstein, Michael B.; Hodge, James W. (Frontiers in Oncology, 2012)
Radiation has long been the standard of care for many types of cancer. It is employed to locally eradicate tumor cells as well as alter tumor stroma with either curative or palliative intent. Radiation-induced cell damage is an immunologically active process in which danger signals are released that stimulate immune cells to phagocytose and present locally released tumor-associated antigens (TAAs). Recent studies have indicated that radiotherapy can also induce immunogenic modulation; an alteration in the phenotype of cancer cells that remain after treatment and renders these cells more sensitive to immune mediated attack.. These cells upregulate TAAs as well as markers, including MHC and costimulatory molecules, that make them much more immunostimulatory. As our understanding of the immunomodulatory effects of radiation has improved, interest in combining this type of therapy with immune-based therapies for the treatment of cancer has grown. Therapeutic cancer vaccines have been shown to initiate the dynamic process of host immune system activation, culminating in the recognition of host cancer cells as foreign. The environment created after radiotherapy can be exploited by active therapeutic cancer vaccines in order to achieve further, more robust immune system activation. This review highlights preclinical studies that have examined the alteration of the tumor microenvironment with regard to immunostimulatory molecules following different types of radiotherapy, including external beam radiation, radiolabeled monoclonal antibodies, bone-seeking radionuclides, and brachytherapy. We also emphasize how combination therapy with a cancer vaccine can exploit these changes to achieve improved therapeutic benefit. Lastly, we describe how these laboratory findings are translating into clinical benefit for patients undergoing combined radiotherapy and cancer vaccination.